The strategic effect of debt in dynamic price competition with fluctuating demand - Leslie Neubecker (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2002)
This paper shows that obligations from debt hinder tacit collusion if equity owners are protected by limited liability. In contrast to its advantageous commitment value in short-run competition, leverage reduces profits from infinite interaction. Contrasting uncorrelated shocks with a cyclical demand development, we show that in the first case optimal pricing is anticyclical. With demand cycles, it is anticyclical only if equity holders place a low value on future profits, but procyclical otherwise. In both cases, the cyclicity of prices increases with the debt level. Contrary to traditional wisdom, a lower degree of homogeneity may raise profits of leveraged firms.
urn:nbn:de:bsz:21-opus-18834
Keywords: L41; L13; G32; E32; C73; 330; capital structure; dynamic competition; collusion; Preiswettbewerb; Kapitalstruktur; Kollusion; Preiswettbewerb; Oligopol; Wettbewerbsbeschränkung; Kapitalstruktur; Verbindlichkeiten; Konjunktur; Dynamisches Spiel; Theorie